Representasi Ibu Ideal pada Media Sosial (Analisis Multimodality pada Akun Instagram @andienippekawa) - Ruvira Arindita (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
The dynamics of social media has given impact to society members, including mothers. The daily life of a celebrity who have become mothers can be seen through the Instagram timeline every day. In order to understand the purpose of the Instagram postings from celebrity mothers, the researcher is using the multimodality analysis/ social semiotics method from Kress and Van Leeuwen. After that, the researcher uses the representation analysis by Stuart Hall to comprehend how the picture of an ideal mother is represented on social media. The result of this research shows that Andien Aisyah as the celebrity, posted her daily activities with her son through her special account dedicated for photos of her mothering experience is to get the acknowledgment of ideal mother from society.